Functional characterization of the human tRNA methyltransferases TRMT10A and TRMT10B. Issue 11 (11th May 2020) - Vilardo, Elisa; Amman, Fabian; Toth, Ursula; Kotter, Annika; Helm, Mark; Rossmanith, Walter
Abstract: The TRM10 family of methyltransferases is responsible for the N 1 -methylation of purines at position 9 of tRNAs in Archaea and Eukarya. The human genome encodes three TRM10-type enzymes, of which only the mitochondrial TRMT10C was previously characterized in detail, whereas the functional significance of the two presumably nuclear enzymes TRMT10A and TRMT10B remained unexplained. Here we show that TRMT10A is m 1 G9-specific and methylates a subset of nuclear-encoded tRNAs, whilst TRMT10B is the first m 1 A9-specific tRNA methyltransferase found in eukaryotes and is responsible for the modification of a single nuclear-encoded tRNA. Furthermore, we show that the lack of G9 methylation causes a decrease in the steady-state levels of the initiator tRNA iMet-CAT and an alteration in its further post-transcriptional modification. Our work finally clarifies the function of TRMT10A and TRMT10B in vivo and provides evidence that the loss of TRMT10A affects the pool of cytosolic tRNAs required for protein synthesis.